APPLYING DEBATE TECHNIQUE WITH REBUTTAL TYPE IN SPEAKING CLASS: PRACTICES AND IMPACTS - Intan Vandani; Ari Dewantara (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2019)
This study aimed at investigating the roles of debate technique with rebuttal type in a speaking class setting. It was motivated by the fact that EFL students tend to be passive in speaking activities in the classrooms. This present study applied quasi-experimental design by involving two groups of students: the experimental group and control group in which each group consisted of 35 students of a vocational high school in Malang, Indonesia. The findings suggest that the use of debate technique with rebuttal type empowers the learning activities to be more effective and interesting. It provides the issues in the pubic area and increases the critical thinking of the students. The implications and suggestions were also discussed.